Scientific approaches to stabilization and formation of the financial state of enterprises - Matsapura, Olena; Kovtun, Anton (Ways to Improve Construction Efficiency, 2024)
This article explores the influence of financial literacy on the economic behavior of individuals and households, emphasizing the importance of financial education in modern society. The study examines the fundamental aspects of financial literacy, including the ability to budget effectively, manage personal savings, invest wisely, and understand financial products such as loans, insurance, and pensions. Particular attention is given to the role of financial literacy in decision-making processes that impact long-term financial stability and economic security. The research highlights the growing significance of financial knowledge in an era of economic uncertainty, rapid technological advancements, and increasing financial complexity. The study discusses common challenges associated with low financial literacy, such as excessive debt, poor investment decisions, vulnerability to financial fraud, and insufficient retirement savings. Furthermore, the article analyzes the correlation between financial literacy and economic well-being, emphasizing that a higher level of financial awareness contributes to better financial planning and risk management. The study also explores global and national initiatives aimed at improving financial literacy, including educational programs, governmental policies, and the role of financial institutions in promoting financial awareness. It highlights best practices in financial education, particularly the integration of financial knowledge into school curricula, workplace training programs, and online learning platforms. The findings of this research underscore the necessity of continuous financial education across different age groups and socioeconomic backgrounds. The article argues that increasing financial literacy is essential for fostering responsible financial behavior, reducing economic disparities, and ensuring overall financial resilience. In conclusion, the study provides practical recommendations for enhancing financial education and suggests effective strategies for improving financial awareness at both individual and institutional levels.